A step up therapeutic regimen for chronic post-Pfannenstiel pain syndrome. (December 2018) - Verhagen, Tim; Loos, Maarten J.; Mulders, Leon G.; Scheltinga, Marc R.; Roumen, Rudi M.
Abstract: Objective: Up to 8% of patients undergoing surgery via a Pfannenstiel incision may develop chronic inguinal pain. This type of pain is frequently caused by inguinal nerve entrapment and may strongly interfere with daily functioning. We report our long term experience of a step up approach using tender point infiltration and surgical neurectomy for intractable neuropathic post-Pfannenstiel groin pain. Study design: A retrospective database analysis identified patients with neuropathic groin pain due to iliohypogastric and/or ilioinguinal nerve entrapment following a Pfannenstiel incision in a single center between 2000 and 2015. Patients who underwent a neurectomy completed a previously published questionnaire including preoperative pain characteristics, pain reduction (5-point Verbal Rating Scale (VRS) and percentages), functional impairment, complications, recurrence of pain and current need for pain medication. Results: Data of 186 women treated for chronic post-Pfannenstiel neuralgia during this 15 year time period were available. Pain reduction following tender point infiltration was successful in 24 patients (13%). In total, 134 of 144 women who underwent a neurectomy were available for follow up via the questionnaire, and 101 responded (response rate 75%). Median age was 52 years (49–54). Before operation, 87% (n = 88) suffered from (very) severe pain (median VRS of 4, range 3–5). Almost 5 years after the operation (median 57 months, range 8–189), 54% (n = 55) had no or only mild pain (p < 0.001). Two of three women reported at least >50% pain reduction and improvement of daily functioning. Eight patients (8%) experienced recurrence of pain after an initial substantial pain reduction. Conclusions: A step-up approach of tender point infiltration and surgical neurectomy is an effective treatment option in the majority of women with chronic post-Pfannenstiel pain syndrome. Surgeons, gynecologists and pain specialists should consider adopting this treatment regimen for chronic post-Pfannenstiel pain due to nerve entrapment.